Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex]E= \frac{1}{2} mv^2+mgh\ /\cdot2\\\\2E=mv^2+2mgh\\\\2E=m(v^2+2gh)\ /:(v^2+2gh)\\\\m= \frac{2E}{v^2+2gh} [/tex]
[tex]E= \frac{1}{2}mv^2+mgh \ \ / \cdot 2\\ \\ 2 \cdot \frac{1}{2}mv^2+ 2\cdotmgh = 2\cdot E\\ \\ mv^2+2mgh= 2E \\ \\m(v ^2+2gh)= 2E \\ \\ m=\frac{2E}{v ^2+2gh}[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.